Detoxification of Lignocellulosic Hydrolysates by in situ Formation of Fe(0) Nanoparticles on Activated Carbon - Sajab, MS; Santanaraj, J; Mohammad, AW; Kaco, H; Harun, S (North Carolina State Univ Dept Wood & Paper Sci, 2024)
The breakdown of lignocellulosic biomass into fine chemicals is an essential subsequence process of bioconversion technology. However, the manner of decomposition can contribute significantly to inefficiency of the overall conversion. Certain low molecular weight byproducts of the lignin and hemicellulose within lignocellulosic hydrolysate are toxic, making it necessary to carry out a complicated detoxification process. In this study, detoxification of hydrolysate was performed by the adsorption and catalytic oxidation, as well as the integration of both techniques on the targeted compounds of acid-soluble lignin (ASL) and synthetic furfural. In spite of the high selectivity of its adsorption and catalytic oxidation, by relying on just these techniques, the hydrolysate was unable to completely remove ASL and furfural. However, by depositing Fe(0) nanoparticles on the surface active sites of the adsorbent, the integration of the adsorption-oxidation technique provided sufficient performance in the removal of ASL and furfural.